ChemInform Abstract: High‐Performance Silicon Photoanodes Passivated with Ultrathin Nickel Films for Water Oxidation. Issue 6 (11th February 2014) - Kenney, Michael J.; Gong, Ming; Li, Yanguang; Wu, Justin Z.; Feng, Ju; Lanza, Mario; Dai, Hongjie
Abstract Deposition of a thin nickel film (approximately 2 nm thick) on n‐type silicon with its native oxide yields a high‐performance metal‐insulator‐semiconductor photoanode for photoelectrochemical water oxidation in both aqueous KOH (pH 14) and aqueous borate buffer (pH 9.5) solutions.